DEEP EUTECTIC SOLVENTS FOR CO₂ CAPTURE IN POST-COMBUSTION PROCESSES - MIHĂILĂ, Eliza Gabriela; CONSTANTINESCU ARUXANDEI, Diana; DONCEA, Sanda Maria; OANCEA, Florin; DINCĂ, Cristian (Studia Universitatis Babeș-Bolyai Chemia, 2021)
CO₂ emissions represent an actual problem for the environment. Additionally, the new demands for all chemical and physical processes request to be more eco-friendly. In this work, deep eutectic solvents (DESs), a relatively new class of solvents, were used for CO₂ capture and desorption. DESs are more environmentally friendly than classical solvents. Two choline chloride-based DES – ethaline (ChCl:EG, 1:2 molar ratio) and reline (ChCl:U, 1:2 molar ratio) were prepared and characterized before studying their CO2 absorption – desorption capacity. The formation of eutectics was confirmed by FT-IR analysis and DESs were characterized in terms of pH, density, viscosity, refractive index, and electrical conductivity. The tests showed that ethaline had better CO₂ absorption and desorption capacity than reline, which could be explained by several parameters.